2015
DOI: 10.1155/2015/723515
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin: A Promising Medicinal and Nutritional Ingredient

Abstract: Fucoxanthin, an allenic carotenoid, can be isolated from edible brown seaweeds. Recent studies have reported that fucoxanthin has many physiological functions and biological properties, such as antiobesity, antitumor, antidiabetes, antioxidant, anti-inflammatory, and hepatoprotective activities, as well as cardiovascular and cerebrovascular protective effects. Therefore, fucoxanthin can be used as both medicinal and nutritional ingredient to prevent and treat chronic diseases. Although fucoxanthin possesses ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 69 publications
1
103
0
3
Order By: Relevance
“…However, UV filters or boosters should be stable under UV exposure, since their exposure to sunlight might lead to photodegradation reactions that can compromise their physical properties and lead to the formation of undesirable photoproducts [42]. Zhang and Tang [43] discussed that the instability of carotenes is related to the poly chain conjugate and its susceptibility to oxidation, isomerization by heat, light, and chemical interactions. After analyzing the chemical UVA/VIS photoinstability of fucoxanthin, with degradation being over the acceptable range of 20% after a 6 J/cm 2 UVA dose, we added fucoxanthin at 0.5% to a sunscreen formulation to assess photostability at a 27.5 J/cm 2 UVA dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, UV filters or boosters should be stable under UV exposure, since their exposure to sunlight might lead to photodegradation reactions that can compromise their physical properties and lead to the formation of undesirable photoproducts [42]. Zhang and Tang [43] discussed that the instability of carotenes is related to the poly chain conjugate and its susceptibility to oxidation, isomerization by heat, light, and chemical interactions. After analyzing the chemical UVA/VIS photoinstability of fucoxanthin, with degradation being over the acceptable range of 20% after a 6 J/cm 2 UVA dose, we added fucoxanthin at 0.5% to a sunscreen formulation to assess photostability at a 27.5 J/cm 2 UVA dose.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning algal lipids, fucoxanthin 22 ( Figure 5), a xanthophyll-like carotenoid, is one of the most studied metabolites because of its beneficial health effects [18,103,132]. Indeed, there are many published reviews and research articles demonstrating and extolling, among others, the nutraceutical, antioxidant, anticancer, anti-obesity, antidiabetic, antimicrobial, and cardiovascular protective effects of fucoxanthin 22 [103,[132][133][134][135][136][137][138][139]. It is intended here to review the most relevant in vivo studies with pure fucoxanthin, highlighting the impact that each one had on the process of development of fucoxanthin as a drug with many potential therapeutic uses.…”
Section: Fucoxanthinmentioning
confidence: 99%
“…In fact, cooked wakame has a higher FXN concentration than fresh samples [106], due to improved bioavailability upon cooking [37]. With regard to toxicity, most seaweeds are edible, and thus FXN isolated from seaweeds could be considered as a safe pharmaceutical ingredient [107]. Furthermore, a clinical trial reported no abnormalities or adverse effects exhibited by individuals who ingested FXN [95].…”
Section: Therapeutic Potential Of Fucoxanthin In Obesitymentioning
confidence: 99%
“…ASX showed health-promoting potential, such as considerable preventive and curative abilities against oxidative stress-related diseases including obesity [107]. It was suggested that ASX prevented HFD-induced obesity by lowering plasma triglycerides, total cholesterol levels, body weight, and adipose tissue size.…”
Section: Astaxanthin and Obesitymentioning
confidence: 99%